The Biosorption Features of Cr (VI) Ions by Dried Biomass of a Facultative Anaerobic Bacillus cereus Strain Pf-1 - , Paul Fabrice Nguema; , Zejiao Luo; , Zachari Mohamadou Mounir; , Lian Jing Jing (Archives of Current Research International, 2019)
Many studies were undertaken on the biosorption potential of different kinds of biomaterials. However, there is a paucity of data regarding the biosorption mechanism of Cr (VI) using dried cells. In our study, the removal of Cr (VI) from aqueous solution was investigated in a batch system by the dried biomass of a chromium-resistant bacterium isolated from activated sludge samples. Equilibrium and kinetic experiments were undertaken at various initial metal concentration, pH, and biosorbent dosage. Bacillus cereus biomass was characterized using Energy-Dispersive X-ray (EDX), Scanning Electron Microscope (SEM) and Fourier Transform Infrared Spectroscopy (FTIR). Biosorption process was found to be pH dependent. The optimum pH was found to be 2.0. The Langmuir and Freundlich were considered to identify the isotherm that could better describe the equilibrium adsorption of Cr (VI) onto the biomass. Langmuir and Freundlich models fitted our experimental data. The suitability of the pseudo-first order and pseudo-second order kinetic models for the biosorption of Cr (VI) onto Bacillus cereus was also performed. The mechanism for the adsorption was studied by fitting the kinetic data with the Boyd plot and intra-particle diffusion model. External mass transfer was found to be the rate-determining step. Based on the ionic nature of the metal, the intra-particle diffusion and extent of film diffusion varied.